1998
DOI: 10.1006/dbio.1998.8879
|View full text |Cite
|
Sign up to set email alerts
|

Disregulation of Ocular Morphogenesis by Lens-Specific Expression of FGF-3/Int-2 in Transgenic Mice

Abstract: FGF-3, originally named int-2, was discovered as an oncogene frequently activated in mammary carcinomas resulting from the chromosomal integration of the mouse mammary tumor virus (MMTV). Int-2 was later designated FGF-3 based on sequence homology with other members of the fibroblast growth factor (FGF) family. FGF-1 is the prototypical member of the FGF family, and is the only family member which activates all known FGF receptor isoforms. Transgenic mice expressing in the lens a form of FGF-1 engineered to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…4). The anterior cells did not elongate as seen in FGF-overexpressing lenses (Robinson et al, 1995b;Robinson et al, 1998), nor did they exit from the cell cycle. Instead, BrdU incorporation assays showed that there was a two-fold increase of S-phase cells in the Rastransgenic lenses when compared to nontransgenic lenses (Fig.…”
Section: Constitutively Active Ras Induces Lens Cell Proliferation Bumentioning
confidence: 91%
“…4). The anterior cells did not elongate as seen in FGF-overexpressing lenses (Robinson et al, 1995b;Robinson et al, 1998), nor did they exit from the cell cycle. Instead, BrdU incorporation assays showed that there was a two-fold increase of S-phase cells in the Rastransgenic lenses when compared to nontransgenic lenses (Fig.…”
Section: Constitutively Active Ras Induces Lens Cell Proliferation Bumentioning
confidence: 91%
“…When targeted to adult organs (i.e. mammary glands, male reproductive tract, lens of eyes and lungs), FGF-3 induces epithelial hyperplasia (Muller et al, 1990;Ornitz et al, 1991;Stamp et al, 1992;Robinson et al, 1998;Zhao et al, 2001). Taken together, these studies demonstrate that if FGF-3 is inappropriately expressed, it may activate dormant pathways that can then severely perturb normal growth and development.…”
Section: Introductionmentioning
confidence: 98%
“…Treatment of cultured lens epithelial explants with FGF1 or FGF2 stimulates cell proliferation at lower doses and fiber cell differentiation at higher doses McAvoy, 1987, 1989;McAvoy and Chamberlain, 1989;Schulz et al, 1993;Le and Musil, 2001). Overexpression of FGF1,3,4,7,8,or 9 in the lens fiber cells of transgenic mice causes the neighboring epithelial cells to transform into fiber-like cells in vivo (Lovicu and Overbeek, 1998;Robinson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%